Real-Time Gamma Correction Procedure - Al-Hamadi, Faisel; Al-Ani, Mahfoth (Iraqi Journal of Science, 2025)
In the current research work real time gamma correction (contrast balancing) procedure were performed. The motivation behind this research work is to reproduce an accurate image on the monitor for an uncorrected image on a particular computer system. But, in the real world, it isn’t quite this simple, especially when an image needs to look good on different systems, or platforms because most computers, or more specifically, most computer systems, do not work in exactly the same way. However, the current work exploit the advantage that the most monitors work in about the same way with respect to gamma correction to reproduce correction image. Different images from real world were tested using current procedure to illustrate efficiency of it which give good results.